The Effect of Local Organic Fertilizer from Rubber Processing Waste on the Yield of Rubber Plants - Simanjuntak, Ernawati; Prasetyo, Prasetyo; Hartal, Hartal (Akta Agrosia, 2018)
Rubber plant is an important industrial crop, as for economic community and a source of non-oil foreign exchange for the country.  In Indonesia, 85% rubber planting area is community rubber plantation with its productivity is still very low (700 - 900 kg ha-1 year-1), compared to its potential which can be more than 1,500 kg ha-1 year-1.  The low productivity of community rubber plantation is because of the lack of proper handling and maintenance of their plants.  Efforts is needed to improve the quality and productivity of community rubber plantation so as to compete in international trade by improvement on planting, maintenance, latex post-harvesting from the garden to the final processing stage.  This research utilizes solid waste from rubber processing factory that is local organic fertilizer (LOF) which is usually merely dumped and become source of environment contaminant.  The objective of this study was to determine the optimum dosage of rubber mill waste to the yield of rubber plants.  The research was carried out at farmer’s plantation of Tanjung Tengah village, Sub-district of Pondok Kelapa, Central Bengkulu, from May to August 2016.  The experiment was arranged in a Randomized Complete Block Design (RCBD) with four replications and 6 levels of LOF as the treatments i.e. 0, 10, 20, 30, 40 and 50 kg tree-1 equal to 0, 5, 10, 15, 20 and 25 tons ha-1, respectively.  The results showed that the effect of several doses of organic fertilizer of rubber waste to rubber plants had no effect on latex volume, stem girth, latex weights, latex slab weight, and dry weight.  The yield of rubber even tended to decrease as the increase of dose of LOF.  This was supposedly because the rubber plant is an annual crop so takes a long time to show the response of the treatment.Keywords: rubber sap, waste, compost fertilizer